STRUCTURAL AND FUNCTIONAL CARDIOVASCULAR REMODELLING IN ARTERIAL HYPERTENSION - S. V. Gurgenyan; K. G. Adamyan; S. Kh. Vatinyan; K. G. Nikogosyan; P. A. Zelveyan (Российский кардиологический журнал)
In total, 43 patients with essential arterial hypertension (EAH) and 34 patients with isolated systolic arterial hypertension (ISAH) underwent echocardiography, Doppler echocardiography (Hewlet-Pacard Sonos 100, USA), and pulse wave velocity (PWV) assessment (Complier-2, France). All participants were divided into two groups: Group I – with concentric left ventricular hypertrophy (LVH): 27 (62,8%) EAH patients and 12 (35,3%) ISAH patients; and Group II – with eccentric LVH: 16 (37,2%) EAH patients and 22 (64,7%) ISAH patients. In EAH and ISAH, respectively, the most prevalent geometric LV models were concentric and eccentric LVH. Left atrium diameter and right ventricular (RV) outflow tract size were increased in all Group II patients. PWV was increased in both EAH and ISAH patients, to a greater extent among the latter. There was a positive correlation between systolic blood pressure, PWV and LVH parameters. In addition, there was a negative correlation between PWV and relative wall thickness (RWT). Diastolic LV function was impaired in all participants, while Group II patients demonstrated systolic LV dysfunction and diastolic RV dysfunction. LV myocardial mass index was inversely associated with E/A peak ratio. The study described the features of cardiovascular remodelling in EAH and ISAH. Typical structural and functional parameters of heart adaptation to increased workload were specified. The patients at high risk of congestive heart failure were identified.